Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s10067-019-04562-w
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse pruritic erythema as a clinical manifestation in anti-SAE antibody-associated dermatomyositis: a case report and literature review

Abstract: Anti-small ubiquitin-like modifier-1 activating enzyme (anti-SAE) antibodies have been recently discovered especially for myosin and identified as dermatomyositis (DM) marker. The frequency of anti-SAE antibodies in DM patients is extremely low. Diffuse pruritic erythema may be one kind of clinical manifestations of DM with anti-SAE antibodies. In this report, a 48year-old female patient with amyopathic dermatomyositis (ADM) carrying anti-SAE antibodies presented diffuse pruritic erythema for 5 months. Diffuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…As has been noted in other antibody specificities, there may be a difference in presentation depending on the ethnic background (18,19). A comparison of Eastern and Western case descriptions suggests that there is a higher risk for diffuse erythema, dysphagia, ILD, and malignancy in Eastern groups (14). The Johns Hopkins cohort used in this study more closely resembles Western cohorts given our predominantly Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
“…As has been noted in other antibody specificities, there may be a difference in presentation depending on the ethnic background (18,19). A comparison of Eastern and Western case descriptions suggests that there is a higher risk for diffuse erythema, dysphagia, ILD, and malignancy in Eastern groups (14). The Johns Hopkins cohort used in this study more closely resembles Western cohorts given our predominantly Caucasian population.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-SAE1-antibodies are also associated with CADM and skin features (80% of cases) with Gottron’s papules (64%), Gottron’s sign (64%), heliotrope rash (82%) and a distinct diffuse pruritic erythema, which is more common in Asians (50% of cases) than Caucasians (7.3%) 9 14 26. Anti-SAE1 antibodies are also associated with dysphagia (78%), higher rates of malignancy compared with other forms of DM (18.7% to 57% vs 9.4%) and less severe forms of ILD 9 15 26 27. There are no known reports of cardiomyopathy associated with anti-SAE1 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In the acute phase, the dermatosis is typically itchy and sore. Patients who carry the SAE antibody are especially prone to diffuse, pruritic erythema 22 . One study has reported SAE‐positive patients with a symmetrical area of sparing each side of the upper back, the so‐called ‘angel wings’ sign 23 (Fig.…”
Section: Erythema Of the Torsomentioning
confidence: 99%